Quantum Cryptography to Secure Financial Data - Sarah Williams; David Martin; Jessica Green (Journal of Tecnologia Quantica, 2024)
The background of this research focuses on the security challenges of financial data in the era of quantum computing, which can threaten traditional encryption systems. With the advancement of quantum computing technology, quantum cryptography is considered a potential solution to protect sensitive data from more sophisticated eavesdropping threats. The purpose of this study is to evaluate the effectiveness of the quantum key distribution protocol (QKD) in securing financial data and analyze its advantages and disadvantages in this context. The method used is a performance simulation of the three main QKD protocols (BB84, E91, and B92) to measure key delivery time, security level, and computing resource usage. The results show that the E91 protocol offers a higher level of security than BB84 and B92, although it requires longer delivery times and more resources. The conclusion of this study emphasizes that although quantum cryptography has great potential for securing financial data, its practical application still faces various challenges, especially in terms of efficiency and necessary resources. Further research is needed to optimize these protocols and overcome technical and cost barriers to implementation on a financial industry scale.